Association of TGFβ1, TNFα, CCR2 and CCR5 gene polymorphisms in type-2 diabetes and renal insufficiency among Asian Indians - Gupta Arvind; Ammini AC; Kumar KM Prasanna; Tiwari Arun K; Prasad Pushplata; Gupta Rajeev; Thelma BK (BMC, 2007)
Abstract Background Cytokines play an important role in the development of diabetic chronic renal insufficiency (CRI). Transforming growth factor β1 (TGF β1) induces renal hypertrophy and fibrosis, and cytokines like tumor necrosis factor-alpha (TNFα), chemoattractant protein-1 (MCP-1), and regulated upon activation and normal T cell expressed and secreted (RANTES) mediate macrophage infiltration into kidney. Over expression of these chemokines leads to glomerulosclerosis and interstitial fibrosis. The effect of MCP-1 and RANTES on kidney is conferred by their receptors i.e., chemokine receptor (CCR)-2 and CCR-5 respectively. We tested association of nine single nucleotide polymorphisms (SNPs) from TGFβ1, TNFα, CCR2 and CCR5 genes among individuals with type-2 diabetes with and without renal insufficiency. Methods Type-2 diabetes subjects with chronic renal insufficiency (serum creatinine ≥ 3.0 mg/dl) constituted the cases, and matched individuals with diabetes of duration ≥ 10 years and normoalbuminuria were evaluated as controls from four centres in India. Allelic and genotypic contributions of nine SNPs from TGFβ1, TNFα, CCR2 and CCR5 genes to diabetic CRI were tested by computing odds ratio (OR) and 95% confidence intervals (CI). Sub-analysis of CRI cases diabetic retinopathy status as dependent variable and SNP genotypes as independent variable in a univariate logistic regression was also performed. Results SNPs Tyr81His and Thr263Ile in TGF β1 gene were monomorphic, and Arg25Pro in TGF β1 gene and Δ32 polymorphism in CCR5 gene were minor variants (minor allele frequency <0.05) and therefore were not considered for case-control analysis. A significant allelic association of 59029G>A SNP of CCR5 gene has been observed and the allele 59029A seems to confer predisposition to development of diabetic CRI (OR 1.39; CI 1.04-1.84). In CRI subjects a compound group of genotypes "GA and AA" of SNP G>A -800 was found to confer predisposition for proliferative retinopathy (OR 3.03; CI 1.08-8.50, p = 0.035). Conclusion Of the various cytokine gene polymorphisms tested, allele 59029A of CCR5 gene is significantly associated with diabetic renal insufficiency among Asian Indians. Result obtained for 59029G>A SNP of CCR5 gene is in conformity with reports from a Japanese population but due to sub-optimal power of the sample, replication in larger sample set is warranted.